Метал доби пізньої бронзи з Тернопільського краєзнавчого музею - Гошко, Г.Ю. (Археологія, 2006)
У статті подано висновки технологічного вивчення двох невеликих колекцій бронзових виробів культур Ноа і висоцької із фондів Тернопільського музею. До сьогодні такі дослідження майже не проводилися. В статье приведены результаты технологического изучения двух небольших коллекций бронзовых изделий культур Ноа и высоцкой из фондов Тернопольского музея. До настоящего времени такие исследования почти не проводились.
В коллекцию вошли, в основном, украшения, а также предметы домашнего обихода — нож-бритва, проколка и бритва. Учитывая характерные технологические особенности бронзовых предметов для каждого памятника и химическое сходство всего металла, сделан вывод о местном производстве всех изделий. The article summarizes the results of technological study of two small collections of bronze artifacts of Noa and Vysotska cultures from the funds of museum in Ternopil. Until recently such studies were practically not undertaken.
The collection consists mostly of jewelry. Among household utensils there is a razor-knife and a razor. Taking into consideration charecteristic technological peculiarities of the bronze items of each site and chemical resemblance of all the metal articles it is concluded about the local manufacture of all the items.